Investigation of Adsorption of 5-Fluorouracil and 5-Bromouracil onto Sepiolite and Loughlinite: An IR Spectroscopic Study - Akyuz, Sevim; Akyuz, Tanil; Akalin, Elif (Asian Journal of Chemistry, 2014)
The adsorption of 5-fluorouracil (5FU) and 5-bromouracil (5BrU) by sepiolite and loughlinite (natural Na-sepiolite) has been investigated using FT-IR spectrometry. The spectroscopic results indicate that 5-halogenouracils adsorbed on sepiolite and loughlinite are coordinated to surface hydroxyls and/or to Lewis acidic centers by hydrogen bonding interaction through the oxygen lone pairs. Some intensity and frequency changes in the OH stretching and deformation bands of surface hydroxyls (Si-OH) of the 5-fluorouracil and 5-bromouracil treated sepiolite and loughlinite were observed. Adsorption capacity of the sepiolite is found to be higher than loughlinite for 5-halogenuracils. Moreover adsorption capacity of clays were found to decrease in the order 5-fluorouracil > 5-bromouracil.